Competence and Competence Development - Cohen-Scali, Valerie (Study guides in Adult Education, 2012)
What are today's main concepts and theories - and the main stakes - associated with the issue of competences in organisations? Several topics are discussed, including competence issues regarding the evolution of work, professionalisation, competence evaluation, competence management, and the competences of adult educators and trainers, as well as European policies regarding competence needs and development. From the Contents: Changes in Work and Competences Professionalisation and the Development of Competences in Education and Training The Role of Professional Didactics in Skills Development for Training and Education Professionals Competence Evaluation Processes in Adult Education Competence Management and Adult Education Changes in Vocational Training and New Models of Competences for Individuals